2016
DOI: 10.3168/jds.2016-11133
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of liposome-entrapped lemongrass oil on the growth of Listeria monocytogenes in cheese

Abstract: Listeria monocytogenes infection in dairy products is of mounting public concern. To inhibit bacterial growth, we engineered stimuli-responsive liposomes containing lemongrass oil for this study. The controlled release of liposome-entrapped lemongrass oil is triggered by listerolysin O, secreted by L. monocytogenes. We investigated the antibiotic activities of lemongrass oil liposomes against L. monocytogenes in cheese. We also assessed their possible effects on the quality of the cheese. Liposomes containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…It was also reported that lemongrass oil increases the shelf life of different fruits like guava [Murmu & Mishra, 2018], strawberries [Kahramanoglu, 2019], table grapes [Sonker et al, 2014], apples [Frankova et al, 2016;Jo et al, 2014] as well as fruit juice [Tyagi et al, 2014]. It was also found effective in preserving processed foods like cheese [Cui et al, 2016]. A recent report has indicated that lemongrass essential oil may in uence lactic cultures in dairy products [Farias et al, 2019], which may curb its applicability in this sector of food industry.…”
Section: Lemongrass Essential Oil Uses For Food Preservationmentioning
confidence: 99%
“…It was also reported that lemongrass oil increases the shelf life of different fruits like guava [Murmu & Mishra, 2018], strawberries [Kahramanoglu, 2019], table grapes [Sonker et al, 2014], apples [Frankova et al, 2016;Jo et al, 2014] as well as fruit juice [Tyagi et al, 2014]. It was also found effective in preserving processed foods like cheese [Cui et al, 2016]. A recent report has indicated that lemongrass essential oil may in uence lactic cultures in dairy products [Farias et al, 2019], which may curb its applicability in this sector of food industry.…”
Section: Lemongrass Essential Oil Uses For Food Preservationmentioning
confidence: 99%
“…lemongrass, lemon myrtle, lemon verbena, Litsea cubeba, lemon tea tree and melissa) have shown antimicrobial activity (Hu et al, 2019;Naik et al, 2010;Nirmal et al, 2018;Sultanbawa et al, 2009). Its isomers showed antimicrobial activity on Gram-positive, Gram-negative and post-harvest pathogens (Fancello et al, 2016;Lu et al, 2017;Saddiq and Khayyat, 2010); antimicrobial activity of encapsulated essential oils of lemongrass and lemon myrtle has been studied on Gram-positive (Enterococcus faecalis, Listeria monocytogenes and Staphylococcus aureus) and Gram-negative (Escherichia coli, Pseudomonas aeruginosa, Salmonella enteritidis and Salmonella typhimurium) (Cui et al, 2016;Huynh et al, 2008;Leimann et al, 2009;Liakos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Inoculated pork samples with no treatments were tested as controls. Finally, the samples were taken out every 3 days and blended with sterile water (1:9, wt/wt) for the microbial analysis via the plate colony‐counting method (Cui, Wu, & Lin, ).…”
Section: Methodsmentioning
confidence: 99%